Potential of improved irrigation technologies for onion farming in Maharashtra, India: a study of productivity and adoption drivers - Kale, Rajiv B.; Gavhane, Abhishek D.; Gadge, S. S.; Thangasamy, A.; Wayal, Sagar M.; Gaikwad, Shivam Y.; Singh, Sharadveer; More, Sanket J.; Thorat, Vishal S.; Khandagale, Kiran; Mahajan, Vijay (Frontiers in Agronomy, 2025)
The onion cultivation sector in India is grappling with severe challenges, including acute water scarcity, labor shortages, and a sluggish adoption of sustainable agronomic practices. These issues collectively exacerbate the sector’s vulnerability to climate change and production uncertainties. This study critically evaluated the efficacy of an advanced irrigation management practice raised bed with drip irrigation (RBWD) and examined the socio-economic determinants influencing its adoption. Conducted in Maharashtra’s Ghod River basin during the 2022–2023 cropping seasons, the research encompassed 480 farmers equally divided between RBWD adopters and traditional flat bed with flood irrigation (FBWF) practitioners. The findings revealed that RBWD adoption led to significant water savings, averaging 24.52% during the late monsoon and 28.79% in the post-monsoon season while doubling water productivity compared to FBWF systems. Moreover, the implementation of RBWD resulted in a substantial increase in onion bulb yield, ranging from 13.70% to 23.61%, and enhanced bulb quality, particularly in the proportion of marketable bulbs. Family income, land holding, extension contacts and the information source use were the key determinants behind the adoption of the RBWD method. However, significant obstacles such as the high initial investment required for drip irrigation systems and the technical expertise needed for their operation continue to hinder wider adoption. These findings underscore a pressing need to address these barriers through policy interventions and targeted extension services.